Operation Warp Speed: implications for global vaccine security. Issue 7 (July 2021) - ,; Kim, Jerome H; Hotez, Peter; Batista, Carolina; Ergonul, Onder; Figueroa, J Peter; Gilbert, Sarah; Gursel, Mayda; Hassanain, Mazen; Kang, Gagandeep; Lall, Bhavna; Larson, Heidi; et al.
Summary: Several global efforts are underway to develop COVID-19 vaccines, and interim analyses from phase 3 clinical testing have been announced by nine organisations: Pfizer, the Gamaleya Research Institute of Epidemiology and Microbiology, Moderna, AstraZeneca, Sinopharm Group, Sinovac Biotech, Johnson & Johnson, Novavax, and CanSino Biologics. The US programme known as Operation Warp Speed provided US$18 billion in funding for development of vaccines that were intended for US populations. Depending on safety and efficacy, vaccines can become available through mechanisms for emergency use, expanded access with informed consent, or full licensure. An important question is: how will these Operation Warp Speed vaccines be used for COVID-19 prevention in global health settings? We address some key questions that arise in the transition from US to global vaccine prevention efforts and from ethical and logistical issues to those that are relevant to global vaccine security, justice, equity, and diplomacy.